Peranan APBN Dalam Program Jaring Pengaman Sosial Sebagai Instrumen Penanganan Pandemi Covid-19 - Nor Fadillah (Lex Renaissance, 2022)
The Covid-19 pandemic in Indonesia has broadly impacted the lives of the people. Based on the Central Statistics Agency which stated that the rate of economic growth in the 1st Quarter from January to March 2020 only grew by 2.97%. This figure slowed down from 4.79% in the fourth quarter of 2019. The government increased the budget for the Social Safety Net Program as a response to handling Covid by using the state budget as an instrument for recovery due to the Covid-19 pandemic. This study discusses the role of the State Budget and Expenditure Revenue in the form of distribution for the Social Safety Net Program in the perspective of state financial law using normative research methods. The results of the study concluded that the Covid-19 pandemic as a state of emergency has altered the state budget. In the perspective of state financial law, the government's action to increase the state management budget in the Social Safety Net Program is permitted in accordance with the constitution, namely based on Law Number 17 of 2003 and Law Number 2 of 2020, in which the government has the authority to make expenditures for which the budget is not yet available and obtain approval from the DPR at the end of the current budget year. The role of the State Budget in the Social Safety Net program is very important as an instrument for handling the Covid-19 pandemic.Key Words: Covid-19 pandemic; state budget; social safety net AbstrakPandemi Covid-19 di Indonesia menimbulkan dampak yang sangat luas bagi kehidupan masyarakat. Berdasarkan Badan Pusat Statistik yang menyatakan bahwa laju pertumbuhan ekonomi dalam Kuartal 1 Januari sampai Maret tahun 2020 hanya tumbuh 2,97%. Angka ini melambat yaitu dari 4,79% pada Kuartal IV di tahun 2019. Pemerintah menaikkan anggaran untuk Program Jaring Pengaman Sosial sebagai respon penanganan Covid dengan menggunakan APBN sebagai instrumen pemulihan akibat pandemi Covid-19. Penelitian ini membahas tentang peranan Anggaran dan Pendapatan Belanja Negara dalam bentuk penyaluran untuk Program Jaring Pengaman Sosial dalam perspektif hukum keuangan negara dengan metode penelitian normatif. Hasil penelitian menyimpulkan bahwa pandemi Covid-19 sebagai kondisi darurat menyebabkan adanya perubahan APBN. Dalam perspektif hukum keuangan negara, tindakan pemerintah menaikkan anggaran pengelolaan negara dalam Program Jaring Pengaman Sosial diperbolehkan sesuai dengan konstitusi yakni berdasarkan Undang-Undang Nomor 17 Tahun 2003 dan Undang-Undang Nomor 2 Tahun 2020 yakni pemerintah berwenang untuk melakukan pengeluaran yang belum tersedia anggarannya dan memperoleh persetujuan dari DPR pada akhir tahun anggaran berjalan. Peran APBN dalam program Jaring Pengaman Sosial sangat penting sebagai instrumen penanganan pandemi Covid-19. Kata-kata Kunci : Pandemi Covid-19; APBN; jaring pengaman sosial